2017
DOI: 10.1104/pp.17.01089
|View full text |Cite
|
Sign up to set email alerts
|

TsNAC1 Is a Key Transcription Factor in Abiotic Stress Resistance and Growth

Abstract: NAC proteins constitute one of the largest families of plant-specific transcription factors, and a number of these proteins participate in the regulation of plant development and responses to abiotic stress. (), cloned from the halophyte , is a transcription factor gene, and its overexpression can improve abiotic stress resistance, especially in salt stress tolerance, in both and Arabidopsis () and retard the growth of these plants. In this study, the transcriptional activation activity of TsNAC1 and RD26 from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 81 publications
4
31
0
Order By: Relevance
“…Previous studies have demonstrated that the LSH1 and TXT2 expression were repressed in the TsNAC1 overexpression line (Liu et al ., ). In this study, clustering analysis of overlapped genes in the H, N and HN lines revealed that the differential expression levels of LSH1 , TXT2 , PME6 and PME35 correlated with the degree of inhibition of plant growth (Figure a).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous studies have demonstrated that the LSH1 and TXT2 expression were repressed in the TsNAC1 overexpression line (Liu et al ., ). In this study, clustering analysis of overlapped genes in the H, N and HN lines revealed that the differential expression levels of LSH1 , TXT2 , PME6 and PME35 correlated with the degree of inhibition of plant growth (Figure a).…”
Section: Discussionmentioning
confidence: 97%
“…TsNAC1 was reported to recognize CA(T/A)G, which repressed the expression of LIGHT-DEPENDENT SHORT HYPOCOTYLS 1 (LSH1) and UDP-XYLOSYLTRANSFERASE 2 (TXT2) (Liu et al, 2018). ZFHD1 specifically bound to T(T/ A)AATT in Arabidopsis .…”
Section: Tshd1 Functions With Tsnac1 Synergistically In Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Full length Full length protein localizes to both nucleus and plasma membrane; truncated N-terminal form devoid of TM motif is localized to the nucleus - [159] 70 TsNAC1 (Thellungiella halophila) Full length and C-terminal -Role in growth and abiotic stress resistance [163] 71 VND1-5/VASCULAR RELATED NAC-DOMAIN (Arabidopsis thaliana)…”
Section: Mlnac5 (Miscanthus Lutarioriparius)mentioning
confidence: 99%